Karakteristik Berpikir Kritis Siswa dalam Pemecahan Masalah Matematika - KHOLID, IDHAM (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to analyze the characteristics of students' critical thinking in solving mathematical problems. The research method uses a qualitative approach with a case study type. Data collection techniques use observation, interviews, and documentation. The data analysis uses Data Reduction, Display Data, and Verification techniques and the validity of the data uses Triangulation techniques and sources. The results of this study show the characteristics of critical thinking that appear in students include; Mark problem problems, track formulas, sort out concepts of appropriate material, write problem-solving procedures, ask teachers when they don't understand, apply formulas they know. The impact of this research for teachers as evaluation material to train and develop students' critical thinking skills.